Overview of Adolescent Knowledge About HIV/AIDS - Mela, Mela; Maulana, Muhammad Ali; Rahmah, RA Gabby Novikadarti (ProNers, 2024)
Background: Adolescents are a high-risk group for HIV/AIDS due to their vulnerability to engaging in risky behaviors and limited understanding of the disease. Despite global efforts, gaps in adolescent knowledge about HIV/AIDS remain a critical public health challenge, especially in low-resource settings.Objective: This study aimed to assess the level of knowledge about HIV/AIDS among adolescents and identify key factors influencing their understanding.Methods: A descriptive cross-sectional study was conducted involving 120 adolescents from grades 10th and 11th in a senior high school in Kalimantan Barat. Data were collected using structured questionnaires and analyzed descriptively to evaluate respondents' knowledge levels based on demographic factors, such as age, gender, grade level, and sources of information.Results: The findings revealed that most respondents had moderate knowledge of HIV/AIDS, with significant gaps in understanding its transmission and prevention. Social media emerged as the primary source of information, followed by healthcare providers, teachers, and peers. However, the study identified that respondents' knowledge levels varied across demographic categories, highlighting the need for targeted interventions.Conclusion: The study underscores the importance of improving adolescent knowledge about HIV/AIDS through comprehensive education programs. Leveraging accurate and accessible sources of information, particularly through social media and schools, can help bridge knowledge gaps. These efforts are vital in empowering adolescents to make informed decisions and reduce the risk of HIV/AIDS transmission within this vulnerable population.